PENGARUH LINGKUNGAN SOSIAL SISWA DAN KONDISI EKONOMI ORANGTUA TERHADAP PRESTASI BELAJAR SISWA DI SMP NEGERI 9 KOTA PROBOLINGGO - Indira Sandrawati (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2016)
This study aims to know the influence of students’ social environment and parents’ economic level toward learning achievement at SMP Negeri 9 Probolinggo. Sixty eight (68) students were randomly involved as participants in this research. The results showed that social environment, economic level and all both together influenced students’ learning achievement significantly.